BA inhibits LPS-stimulated inflammatory response and apoptosis in human middle ear epithelial cells by regulating the Nf-Kb/Iκbα axis - He Qian; Cai Yanzhi; Kong Meihua (Open Life Sciences)
Otitis media (OM) is a prevalent childhood ear disease characterized by inflammation of the middle ear cavity, which can lead to ear pain, fever, and hearing loss. The pathogenesis of OM is multifaceted, encompassing a variety of factors including bacterial or viral infections, host immune responses, and the function of middle ear epithelial cells. Boswellic acid (BA), a natural triterpene compound extracted from frankincense resin, has been proven to possess significant anti-inflammatory and immunomodulatory effects. This study aims to investigate the effects of BA on lipopolysaccharide (LPS)-stimulated inflammatory responses and apoptosis in human middle ear epithelial cells (HMEECs) and its potential mechanisms. Our findings demonstrated that BA enhances the proliferation of LPS-stimulated HMEECs and concurrently inhibits their apoptosis. In addition, BA blocked LPS-stimulated HMEEC inflammation. Mechanistically, BA suppressed the NF-κB/IκBα axis in LPS-stimulated HMEECs. In conclusion, BA effectively inhibits LPS-stimulated inflammation and apoptosis by mediating the NF-κB/IκBα axis, highlighting its potential as a therapeutic agent for OM.